Nursing of a patient with heart failure treated with umbilical moxibustion combined with acupoint application therapy based on the theory of nourishing Yang in spring and summer (基于"春夏养阳"理论指导运用脐疗法护理1例心力衰竭患者) - LYU Xuejun (吕学军); YU Lijun (郁丽君); YANG Lili (杨丽丽); SONG Libo (宋丽波) (Association of Integrative Nursing, 2024)
This paper summarized the practice of umbilical moxibustion combined with acupoint application therapy based on the theory of nourishing yang in spring and summer for a patient with heart failure. Based on the theory of Traditional Chinese Medicine syndrome differentiation and principle of treatment in line with seasons' change, the patient was treated with the umbilical moxibustion combined with acupoint application therapy. Comprehensive nursing interventions such as daily life support, dietary guidance, and psychological care were carried out during treatment to relieve the clinical symptoms and improve patients' quality of life (本文总结1例基于"春夏养阳"理论指导的脐疗法在心力衰竭患者中的应用效果。基于中医辨证理论指导, 运用因时施治原则, 采取脐疗法隔姜灸联合穴位贴敷, 配合生活指导、饮食指导、心理指导等综合干预, 改善心力衰竭患者不适症状及伴随体征, 提高患者的生活质量。)